Synthesis and Structural Reports of C12H20N2O4 - Gogoi, A.; Hazarika, P.; Konwar, D.; Boruah, R.K. (Asian Journal of Chemistry, 2012)
Present compound C12H20N2O4, a condensation product, is derived from ethylene diamine and methyl acetoacetate using Sn-nanodisks (Sn(HPO4)2·H2O) as catalyst. The crystalline form of these spring-like superstructure solids exhibits a plane layered structure, which is made up of [M(PO4)2]n2n macro anions, potential active anode materials for the lithium-ion battery. The reported compound dimethyl (Z,Z)-3,3'-(ethane-1,2-diyldiimino)dibut-2-enoate, C12H20N2O4 crystallizes in monoclinic C2/c space group with unit cell parameters: a = 19.467(9) Å, b = 5.505(2) Å, c = 13.139(6) Å, b = 111.397(6)º, V = 1311.0(10) Å3, Z = 4.